The Structure and Behavior of Imports of Venezuela - Khan, Mohsin S. (The Review of Economics and Statistics, 1975)
IN the area of international trade, there have been a number of studies designed to explain imports and exports disaggregated by commodities.' These studies, however, all concentrate on the trading patterns of industrial countries and there has been very little in the way of a systematic analysis of the imports and exports by types of commodities for developing countries. There is, of course, an obvious reason for ignoring these countries, and that has to do with the availability, or rather paucity, of adequate data; this data problem is most pronounced in the area of prices of disaggregated imports and exports. Although it is generally believed that the trading patterns of developing countries differ from those of the developed, an empirical examination would be necessary to determine the extent of such a difference. The purpose of this paper is to study the behavior of the imports of Venezuela at both the aggregated and disaggregated levels during the period 1953-1972. Data on imports at a disaggregated level have recently been made available for Venezuela for a nine-commodity breakdown;2 the data include the value and price for each of these categories on an annual basis, as well as the price of the domestic competing product. These nine categories cover some 80% of the total Venezuelan imports. The results of this study should provide information on the behavior of different types of import goods and on the nature and extent of the bias involved in estimates of elasticities based only on aggregate imports.